1997
DOI: 10.1017/s0022112097005636
|View full text |Cite
|
Sign up to set email alerts
|

On the extinction limit and flammability limit of non-adiabatic stretched methane–air premixed flames

Abstract: Extinction limits and the lean flammability limit of non-adiabatic stretched premixed methane–air flames are investigated numerically with detailed chemistry and two different Planck mean absorption coefficient models. Attention is paid to the combined effect of radiative heat loss and stretch at low stretch rate. It is found that for a mixture at an equivalence ratio lower than the standard lean flammability limit, a moderate stretch can strengthen the combustion and allow burning. The flame is extin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
155
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 277 publications
(170 citation statements)
references
References 11 publications
10
155
1
4
Order By: Relevance
“…For a premixed opposed jet flame, Ju et al found a decrease of the extinction stretch rate from ≈1800 s −1 at φ=0.75 to ≈460 s −1 at φ=0.55 [28]. Principal strain rates were determined for the present flow fields, and the lowest absolute values (<500 s −1 ) were found in the vortex centers, where solid-body rotation occurs.…”
Section: Helical Flame Zonementioning
confidence: 64%
See 2 more Smart Citations
“…For a premixed opposed jet flame, Ju et al found a decrease of the extinction stretch rate from ≈1800 s −1 at φ=0.75 to ≈460 s −1 at φ=0.55 [28]. Principal strain rates were determined for the present flow fields, and the lowest absolute values (<500 s −1 ) were found in the vortex centers, where solid-body rotation occurs.…”
Section: Helical Flame Zonementioning
confidence: 64%
“…6, the 2D principal strain rates at the stagnation point were determined as 5620 s −1 (extensive) and 4058 s −1 (compressive). These values are well above the stretch extinction limit of ≈460 s −1 at φ=0.55 [28]. The flame root can, to some extent, withstand the high strain rates because of the locally relatively fuel rich and hot conditions (see Fig.…”
Section: Flame Rootmentioning
confidence: 69%
See 1 more Smart Citation
“…This concern becomes more serious when the ambient pressure increases. Recently, it has become clear that spectral radiation is the dominant loss mechanism for flammability limit [1][2][3][4][5] and it leads to radiation extinction [6][7][8][9], flame bifurcations [10][11][12] and radiation induced instability [13]. Therefore, the effect of radiation heat loss on near limit flames has been extensively studied [1][2][3][4][5][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…낮은 화염신장율의 조건에서 중요시되는 복사 열손실 및 첨가된 CO 2 의 추가적인 복사 열손실을 고려하기 위하 여, 간략화된 모델로서 화염 및 부근의 가스가 광학적으로 매우 얇아 복사에너지를 흡수하지 않는다는 가정이 적용 된 Optically Thin Model(OTM) (15) 이 사용되었다.…”
Section: 서 론unclassified